If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + -2(n + 2) = -7(n + 2) Reorder the terms: 5n + -2(2 + n) = -7(n + 2) 5n + (2 * -2 + n * -2) = -7(n + 2) 5n + (-4 + -2n) = -7(n + 2) Reorder the terms: -4 + 5n + -2n = -7(n + 2) Combine like terms: 5n + -2n = 3n -4 + 3n = -7(n + 2) Reorder the terms: -4 + 3n = -7(2 + n) -4 + 3n = (2 * -7 + n * -7) -4 + 3n = (-14 + -7n) Solving -4 + 3n = -14 + -7n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '7n' to each side of the equation. -4 + 3n + 7n = -14 + -7n + 7n Combine like terms: 3n + 7n = 10n -4 + 10n = -14 + -7n + 7n Combine like terms: -7n + 7n = 0 -4 + 10n = -14 + 0 -4 + 10n = -14 Add '4' to each side of the equation. -4 + 4 + 10n = -14 + 4 Combine like terms: -4 + 4 = 0 0 + 10n = -14 + 4 10n = -14 + 4 Combine like terms: -14 + 4 = -10 10n = -10 Divide each side by '10'. n = -1 Simplifying n = -1
| 8x-13=5x+26 | | 5q-1=-16 | | 3500*x=5000 | | x=4.5+-0.75y | | 9(7+z)=45 | | -3z+9z-7=29 | | x+31=40 | | 9(x+1)+3(7-6x)=16x | | 13y-8y-4=56.20 | | 0=-.25x+6 | | x-0.6=0.4 | | 4y+-3y-6=1 | | 3x-7=10-2x | | 6x+3=8x-11 | | r+(-29)=-38 | | x-1/4=1/8 | | 3(2+x)=0 | | 7d+5d+4d-4= | | x^2-3x+1-x^2+2x+7= | | 2(x-3)-4x=-10 | | -4(9+z)=-52 | | 5b=75 | | x-0.9=0.3 | | f(x)=3(x-2)+7 | | 2a+2=a-10 | | 6y+-2y-7=9 | | 9+8x=-5+x | | 2z+-2z+4=4 | | 7(9+z)=91 | | px(q+5)= | | x+1.2=0.6 | | 9z+7z-5=43 |